Social impact finance - Atbani, Faisal M.; Trullols, Cristina; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
As a result of the recent financial crisis, new ways of doing finance have developed, creating alternatives to the regular financial system. This book explores non-conventional banking and financing mechanisms in detail, with case studies and examples in which these alternative methods have succeeded.
Keywords: Banking; Banks and banking -- Social aspects; Finance